Dimenticanza o annullamento? - Del Pace, Letizia (Il sogno della farfalla, 2019)
By analyzing underlying non-conscious dynamics, the author deals with the issue of children abandoned by parents, which often leads to fatal deaths caused by hyperthermia or dehydration. In this paper is stated how these events should not be considered as acting out, as the parent’s behaviour is not triggered by a conscious willingness to cause their own child’s death. Instead, this article explains how these dramatic facts are determined by the annulment pulsion that parents can act towards their own offspring. This non-conscious dynamic expresses a lack of affection, which can be hidden behind an apparently normal behaviour. Therefore, these events cannot happen to anyone and should not be considered as the result of stressful conditions. The diagnosis of dissociative amnesia, which is commonly stated in these cases, is disproven. On the other hand the author, starting from the classical bleulerian conception, claims that in relation to these events a form of dissociation can be proposed. The annulment pulsion addressed towards the child leads to a dissociation between thoughts and affection, so that the child become an object to merely manage. This is considered as a pathological relationship modality between the parent and the child which can be not only cured but also prevented.